(3eOi eTQhYjI GdJONd GdYScQi GdOhdi ai Gdjef (B/ s - (3CMeO efUhQ YHOGddg CMeO GdaMes; (3eMeO QeVGf MSfjf eMeO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2020)
(3JHMK gPg GdQSGdI ai ehVhY(B: (3eOi eTQhYjI GdJONd GdYScQj GdOhdi ai Gdjef(B: (3h GdPi QCjfG Cf fNhV gPg GdOQGSI HYfhGfgG GdeWQhM ef NdGd CQHYI aUhd(B. (3JVef GdaUd GdJegjOi(B: (3eaghe GdJONd ai GdbGfhf GdOhdi(B: (3h fTCJg h JWhQg GdJGQjNi(B: (3h HjGf eGgjI GdJONd h JMOjO fWGbg(B: (3h GSJNdGU YfGUQg GdCSGSjI(B: (3h YQV UhQI h CTcGdg(B: (3eJVeG HYV GdCeKdI GdhGbYjI ddJONd ef GdSGMI GdOhdjI(B. (3Ced GdaUd GdChd(B: (3abO NUUfGg ddLhGfH GdbGfhfjI GdJi JMce GdJONd GdOhdi(B: (3h JfGhdfG Pdc ef NdGd GdMOjK Yf eHOC SjGOI GdOhdI ai GdbGfhf GdOhdi(B: (3h HjGf eagheg(B: (3h eOi JWhQg ai EWGQ GdJZjQGJ GdOhdjI h ENJdGa fWGbg(B: (3h GdGfJbGd HYO Pdc Edi eHOC YOe GdJONd h HjGf eagheg h NUGFUg GdeejRI(B: (3h eG jQO Ydjg ef GSJKfGAGJ ai Xd GdeYGgOGJ h GdehGKjb GdOhdjI(B. (3CeG GdaUd GdKGfi(B: (3abO JfGhdfG ajg GdJONd GdOhdi GdYScQi ai Gdjef(B: (3ef NdGd SQO h OQGSI LPhQ GdCReI GdjefjI h eSGQgG(B: (3h HjGf aje JeKdJ eHQQGJ GdGFJdGa GdYScQi GdPi JbhOg GdeedcI GdYQHjI GdSYhOjI h GdCSS GdbGfhfjI GdJi GSJfO YdjgG(B: (3h eG cGfJ Ydjg ehGba GdeLJeY GdOhdi ef gPG GdJONd(B. (3CeG GdaUd GdKGdK(B: (3abO NUUfGg dJbjje GdJONd GdOhdi GdYScQi ai Gdjef(B: (3h HjGf eOi eTQhYjJg(B: (3ef NdGd JJHY h QUO GdehGba GdEbdjejI h GdOhdjI ERGA gPG GdJONd GdYScQi(B: (3h Jbjje GdMLL GdbGfhfjI GdPi JSJfO YdjgG Ohd GdGFJdGa GdYScQi h YQV LgGJ GdfXQ ERGAgG(B: (3h GdGfJbGd CNjQG Gdi HjGf eOi eTQhYjI GdJONd GdYScQi ai Gdjef(B. (3CeG NGJeI GdHMK(B: (3abO LGAJ dJTed LedI ef GdfJGFL h GdJhUjGJ GdebJQMIs
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdOhdi, (B2020s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B182-197s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdjs; (3GdJONd GdYScQi GdOhdis; (3Gdjefs; (3eTQhYjIs; (3eLdS GdJYGhf GdNdjLjs; (3eHOG SjGOI GdOhdIs; (3eHOC YOe GdJONd s; (3LGeYI GdOhd GdYQHjIs; (3GdCee GdeJMOIs; (3GdQFjS Gdjefjs; (3GdMb GdTQYjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdOhdjs